До невизначеності в непараметричних схемах ситуацій задач прийняття рішень - Mykhalevich, V. M.; Ivanenko, V. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
Sufficiently broad class of non-parametric problems of decision-making, which is considered from the point of obtaining the criteria of optimality — the relationship of preferences on the solutions, can be divided into two subclasses: problem with uncertainty (equivocation of the solution) and problems without uncertainty (so-called deterministic problems). For such classification criteria of uncertainty existence, which are suggested in this work, are necessary.